Perubahan Bunyi Bahasa Arab Fusha ke dalam Dialek Mesir Pada lagu Tamally Ma’ak - Fina Nur Fadhilah (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2020)
The review was intended to analyze the changing of Arabic language sound Fusha on the language speaker ' Amiyyah of Egypt through the song of Tamally Ma'ak. In this review, Peneliti will use Crowly-owned theories. The data used was the vocabulary obtained from the song of Tamally Ma'ak. The result of this menunjukka is that there is a sound change [Q] as [ʔ] [ʕ] becoming [ʔ], [ħ] becoming [h], [long vocal] became [short vocal], [ʤ] becoming [ɣ], [D̪ ˁ] becoming [d], [s ˁ] becoming [s], [short vocal] into [long vocal], a sound deviation Vocals and consonants, [f] became [b], [ʔ] becoming [b], [Q] becoming [ɣ], a consonant, [ʔ] becoming [t], vocal [a] vocal [Ǝ] and vocal [a] became vocal [u].